Q and the history of early Christianity : studies on Q - Tuckett, Christopher Mark (Edinburgh : Clark, 1996)
"After seeking to establish the existence of Q, Professor Tuckett proceeds to analyse the characteristic features of the Q material. He explores not only what we can learn about the possible 'theology' of Q, but also what we can learn about the social situation of the Christians who valued and preserved this material." "There are discussions of John the Baptist in Q, the eschatology and Christology of Q, the nature of the polemic in Q. An attempt is made to determine how far Q is a 'wisdom' text; and how far Q reflects 'Cynic' ideas."--Jacket
Includes bibliographical references and index. ISBN 0-567-08584-8
Keywords: Q hypothesis (Synoptics criticism)